Analysis and selection of measurement indexes of MWD in rock lithology identification. (28th February 2023) - Zhang, Wenlong; Ren, Jianju; Zhu, Fan; Feng, Jicheng
Highlights: Feedback indexes of roof bolter when drilling two different rocks are measured. The reflect degree of parameters in distinguishing different bricks are obtained. Thrust and torque indexes can clearly show the gaps in the rock sample. Abstract: Based on the measurement indexes monitored by the roof bolter while drilling, the rock properties, fractures and other rock stratum characteristics can be obtained, which provide important basics for risk assessment of underground engineering, design of safety measures and determination of parameters. In this study, the measurement indexes include distance, thrust, torque and vibration in three directions s are measured by various types of sensors in laboratory when drilling two different bricks and their combined sample under fixed rotational speed. Through the research and analysis of the measurement data, the data of different drilling stages are also analyzed, more importantly, the test parameter difference and the obvious degree of the parameters in distinguishing the two types of bricks are obtained. The study results are of great significance for the selection of monitoring measurement indexes of roof bolter while drilling.